Demography of High-Redshift AGN. (16th January 2012) - Fiore, Fabrizio; Puccetti, Simonetta; Mathur, Smita
Abstract : High-redshift AGN holds the key to understanding early structure formation and to probe the Universe during its infancy. We review the latest searches for high-z AGN in the deepest X-ray field so far, the Chandra Deep Field South (CDFS) 4 Msecond exposure. We do not confirm the positive detection of a signal in the stacked Chandra images at the position of z 6 galaxies recently reported by Treister and collaborators (2011). We present z > 3 X-ray sources number counts in the 0.5–2 keV band, obtained joining CDFS faint detections (see Fiore et al. (2011)), with Chandra-COSMOS and XMM-COSMOS detections. We use these number counts to make predictions for surveys with three mission concepts: Athena, WFXT, and a Super-Chandra.